PENGARUH EFEKTIVITAS KOMITE AUDIT DAN MUTU KAP TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2023) - Zelda Annisa Sandhyanasti; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the function of audit committees, including the appointment of public accounting firms (KAP), in overseeing earnings management practices in non-financial companies listed on the Indonesia Stock Exchange in 2022-2023. The control variables used in this study include company size, profitability, leverage, free cash flow, and cash flow from operations. This study utilizes agency theory to generate testable hypotheses, and these hypotheses provide empirical findings.The population of this study comprised all companies in Indonesia, except the financial sector, that included the research variables used in this study and were listed on the Indonesia Stock Exchange in 2022-2023. A sample of 568 companies was obtained using a purposive sampling technique. The data were analyzed using the Structural Equation Model (SEM) approach with the Partial Least Squares (PLS) method in SmartPLS 4.1.1.4 software.The results indicate that neither committee effectiveness nor KAP quality significantly impact earnings management practices. Therefore, these findings indicate that the role of audit committees and the quality of public accounting firms are not yet optimal in curbing earnings management practices. The implications of this research are the need to improve audit committee oversight and appoint qualified public accounting firms to enhance financial reporting transparency.